Palmeiras do Parque Natural do Seringueiro, Acre, Brasil - Ferreira, Evandro (Acta Amazonica, 1998)
Ten genera and 22 palm species were found in the Parque Natural do Seringueiro, municipality of Plácido de Castro, State of Acre, in the southwest Amazon. The park comprises only 45 hectares of area, however the generic and specific diversity found is comparable to that found in the 10,000 hectares Ducke Reserve in central Amazon. This high diversity and the intensive destruction of the forest in Plácido de Castro region demonstrates the urgent necessity for establishing more protected areas to preserve the local flora.
Palms of Parque Natural do Seringueiro, Acre, Brazil
Keywords: Arecaceae; Acre; Native Park; Arecaceae; Acre; Parque Natural